The Cultivating Ethical Communicators: Role-Playing as Character Education for Javanese Linguistic Etiquette Mastery - Mahdum Wiraman; Pinkan Dwi Pravitasari; Faustine Fiona Eka Farah Dewi; Naufal Ishartono; Aris Sukoco (Universitas Muhammadiyah Surakarta, 2025)
This study examines the effectiveness of role-playing pedagogy in enhancing Javanese language proficiency aligned with traditional etiquette principles among fifth-grade students at SD Negeri Pucangan 3. Recognizing that Javanese linguistic-cultural competence serves as both a character-building tool and a vehicle for cultural preservation, the research employed a two-cycle Classroom Action Research (CAR) methodology comprising planning, implementation, observation, and reflection phases. Twenty participants were assessed through performance-based observations using instruments adapted from established protocols, with data analyzed through reduction, systematic presentation, and cyclical interpretation. Initial assessments revealed only 37.5% mastery of etiquette-appropriate Javanese communication, evaluating four key linguistic dimensions: (1) conversational fluency in formal contexts, (2) grammatical accuracy of honorific structures, (3) phonological precision in stratified vocabulary, and (4) contextually appropriate lexico-cultural choices. Post-intervention results demonstrated significant improvement to 71.25% mastery, confirming role-playing's efficacy in developing both linguistic competence and cultural awareness. The findings highlight how experiential learning methods can effectively bridge the gap between language acquisition and cultural transmission, particularly in maintaining indigenous linguistic etiquette among younger generations. Furthermore, the study underscores the pedagogical value of integrating performance-based strategies into character education curricula, suggesting their potential application in other indigenous language preservation contexts. These results contribute to ongoing discussions about culturally responsive teaching methodologies while providing empirical evidence for role-playing as a mechanism for sustaining linguistic heritage and reinforcing the socio-cultural values embedded within stratified language systems like Javanese. The implications extend beyond language education, offering insights into innovative approaches for holistic character development through culturally grounded pedagogies.